'When birds of a feather flock together': synesthetic correspondences modulate audiovisual integration in non-synesthetes. - Parise, C; Spence, C (2009)
BACKGROUND: Synesthesia is a condition in which the stimulation of one sense elicits an additional experience, often in a different (i.e., unstimulated) sense. Although only a small proportion of the population is synesthetic, there is growing evidence to suggest that neurocognitively-normal individuals also experience some form of synesthetic association between the stimuli presented to different sensory modalities (i.e., between auditory pitch and visual size, where lower frequency tones are associated with large objects and higher frequency tones with small objects). While previous research has highlighted crossmodal interactions between synesthetically corresponding dimensions, the possible role of synesthetic associations in multisensory integration has not been considered previously. METHODOLOGY: Here we investigate the effects of synesthetic associations by presenting pairs of asynchronous or spatially discrepant visual and auditory stimuli that were either synesthetically matched or mismatched. In a series of three psychophysical experiments, participants reported the relative temporal order of presentation or the relative spatial locations of the two stimuli. PRINCIPAL FINDINGS: The reliability of non-synesthetic participants' estimates of both audiovisual temporal asynchrony and spatial discrepancy were lower for pairs of synesthetically matched as compared to synesthetically mismatched audiovisual stimuli. CONCLUSIONS: Recent studies of multisensory integration have shown that the reduced reliability of perceptual estimates regarding intersensory conflicts constitutes the marker of a stronger coupling between the unisensory signals. Our results therefore indicate a stronger coupling of synesthetically matched vs. mismatched stimuli and provide the first psychophysical evidence that synesthetic congruency can promote multisensory integration. Synesthetic crossmodal correspondences therefore appear to play a crucial (if unacknowledged) role in the multisensory integration of auditory and visual information.